Prototol for the Prospective Sample Collection for Cancer of Bladder (ProCaB) Trial by the Cancer of the Bladder Leuven (CaBLe) Consortium - Murat Akand; Tim Muilwijk; Ben Van Cleynenbreugel; Thomas Gevaert; Steven Joniau; Frank Van der Aa (European Urology Open Science)
Non–muscle-invasive bladder cancer (NMIBC) is a heterogeneous disease categorized as low, intermediate, high, or very high risk, for which recurrence and progression rates and thus management strategies differ. Current molecular subclassification of bladder cancer (BC) is mainly based on data for muscle-invasive disease, with very few data for NMIBC. A more accurate classification system is needed for better stratification of NMIBC using multiomics and immunohistopathological molecular data alongside clinical data collected in a prospective cohort. ProCaB (Prospective Sample Collection for Cancer of Bladder) is a single-center non-interventional, prospective study recruiting all eligible patients diagnosed with BC in a tertiary center in the Flanders region of Belgium. Clinical data have been collected in a prospective registry since August 2013. Biosamples (blood, urine, and BC tissue) are collected from each patient at diagnosis and are stored at −80°C at BioBank UZ Leuven after appropriate processing according to the protocol. Multiomics (genomics, epigenetics, transcriptomics, proteomics, lipidomics, metabolomics) and immunohistopathology analyses will be performed on appropriate samples. The target is to enroll 300 patients over a 5-yr period, and all patients will be followed for 5 yr. The objective is to create a biobank of samples from patients diagnosed with BC for use in multiomics and immunohistopathological analyses. Results from these analyses, together with long-term clinical data, can be used for comprehensive multilayered molecular characterization of disease recurrence and progression in intermediate- and (very) high-risk NMIBC, identification of multibiomarker panels for better stratification, and identification of a patient subgroup that does not respond to bacillus Calmette-Guérin treatment.This trial is registered on ClinicalTrials.gov as NCT04167332.